Neural Derivates of Canine Induced Pluripotent Stem Cells-Like Cells From a Mild Cognitive Impairment Dog - Chandrasekaran, Abinaya; Thomsen, Barbara Blicher; Agerholm, Jørgen Steen; Pessôa, Laís Vicari de Figueiredo; Godoy Pieri, Naira Caroline; Sabaghidarmiyan, Vahideh; Langley, Katarina; Kolko, Miriam; de Andrade, André Furugen Cesar; Bressan, Fabiana Fernandes; Hyttel, Poul; Berendt, Mette; et al. (Frontiers in Veterinary Science, 2021)
Domestic dogs are superior models for translational medicine due to greater anatomical and physiological similarities with humans than rodents, including hereditary diseases with human equivalents. Particularly with respect to neurodegenerative medicine, dogs can serve as a natural, more relevant model of human disease compared to transgenic rodents. Herein we report attempts to develop a canine-derived in vitro model for neurodegenerative diseases through the generation of induced pluripotent stem cells from a 14-year, 9-month-old female West Highland white terrier with mild cognitive impairment (MCI). Canine induced pluripotent stem cells-like cells (ciPSCLC) were generated using human OSKM and characterized by positive expression of pluripotency markers. Due to inefficient viral vector silencing we refer to them as ciPSCLCs. Subsequently, the ciPSCLC were subjected to neural induction according to two protocols both yielding canine neural progenitor cells (cNPCs), which expressed typical NPC markers. The cNPCs were cultured in neuron differentiation media for 3 weeks, resulting in the derivation of morphologically impaired neurons as compared to iPSC-derived human counterparts generated in parallel. The apparent differences encountered in this study regarding the neural differentiation potential of ciPSCLC reveals challenges and new perspectives to consider before using the canine model in translational neurological studies.